Effect of gamma-radiation on zearalenone—degradation, cytotoxicity and estrogenicity - Calado, Thalita (2020)
Zearalenone (ZEA) is produced in cereals by different species of Fusarium, being a non-steroidal estrogenic mycotoxin. Despite having a low acute toxicity, ZEA strongly interferes with estrogen receptors. Gamma-radiation has been investigated to eliminate mycotoxins from food and feed, showing promising results. The present study aims to investigate the gamma-radiation effect on ZEA at different moisture conditions and to evaluate the cytotoxicity and estrogenicity of the irradiated ZEA. Different concentrations of dehydrated ZEA and aqueous solutions of ZEA were exposed to gamma-radiation doses ranging from 0.4 to 8.6 kGy and the mycotoxin concentration determined after exposure by high performance liquid chromatography (HPLC) with fluorescence detection. Following this, the cytotoxicity of irradiated samples was assessed in HepG2 cells, by measuring alterations of metabolic activity, plasma membrane integrity and lysosomal function, and their estrogenicity by measuring luciferase activity in HeLa 9903 cells. Gamma-radiation was found to be effective in reducing ZEA, with significant increases in degradation with increased moisture content. Furthermore, a reduction of cytotoxicity with irradiation was observed. ZEA estrogenicity was also increasingly reduced with increasing radiation doses, but mainly in aqueous solutions. These results suggest reduction of ZEA levels and of its toxicity in food and feed commodities may be achieved by irradiation.